Cost-effectiveness of pegfilgrastim versus filgrastim for prevention of chemotherapy-induced febrile neutropenia in patients with lymphoma: a systematic review - Girma Tekle Gebremariam; Atalay Mulu Fentie; Kebede Beyene; Beate Sander; Gebremedhin Beedemariam Gebretekle (BMC, 2022)
Abstract Background Febrile neutropenia (FN) is a prevalent and potentially life-threatening complication in patients with lymphoma receiving myelosuppressive chemotherapy. Pegfilgrastim is more effective than filgrastim as prophylaxis for FN. However, its usage has been limited because of its higher cost. Pegfilgrastim's value for money remains unclear. Objective To systematically review the cost-effectiveness of pegfilgrastim compared to filgrastim as a primary or secondary prophylaxis for chemotherapy-induced FN among patients with lymphoma. Methods A systematic literature search was conducted in PubMed, EMBASE, Cochrane Library databases, and Google Scholar. The most widely used economic evaluations (cost-effectiveness analysis, cost-utility analysis and cost-benefit analysis) were included in the review. Data extraction was guided by the Consolidated Health Economic Evaluation Reporting Standards checklist, and the quality of reviewed articles was assessed using the Joanna Briggs Institute (JBI) checklist. Cost-effectiveness data were rigorously summarized and synthesized narratively. Costs were adjusted to US$ 2020. Results We identified eight economic evaluation studies (two cost-utility analyses, three cost-effectiveness analyses, and three studies reporting both cost-effectiveness and cost-utility analyses). Half of these studies were from Europe (n = 4), the other half were from Iran, USA, Canada, and Singapore. Six studies met > 80% of the JBI quality assessment criteria. Cost-effectiveness estimates in the majority (n = 6) of these studies were for Non-Hodgkin Lymphoma patients receiving myelosuppressive chemotherapy with high-risk of FN (> 20%). The studies considered a wide range of baseline FN risk (17-97.4%) and mortality rates (5.8-8.9%). Reported incremental cost-effectiveness ratios ranged from US$ 2199 to US$ 8,871,600 per quality-adjusted life-year (QALY) gained, dominant to US$ 44,358 per FN averted, and US$ 4261- US$ 7251 per life-years gained. The most influential parameters were medication and hospitalization costs, the relative risk of FN, and assumptions of mortality benefit. Conclusions Most studies showed that pegfilgrastim is cost-effective compared to filgrastim as primary and secondary prophylaxis for chemotherapy-induced FN among patients with lymphoma at a cost-effectiveness threshold of US$ 50,000 per QALY gained. The findings could assist clinicians and healthcare decision-makers to make informed decisions regarding resource allocation for the management of chemotherapy-induced FN in settings similar to those studied.